Bedürfnisse im Wandel: Theorie, Zeitdiagnose, Forschungsergebnisse - Hondrich, Karl Otto; Vollmer, Randolph; Arzberger, Klaus (Westdeutscher Verl., 1983)
Literaturverz. S. 274 - 280. - Nebent.: Bedürfnisse